THE EFFECT OF ORGANIC PLANTING TAPE ON THE INSTRUCTION OF WEEED GROWTH IN RICE (Oryza sativa L.) PEATLANDS IN SOUTH SUMATRA REGION - Riri Novita Sunarti (Teknosains, 2022)
Most of the area of South Sumatra Province covering an area of 87,017 km2 is peatland spread across the eastern region, starting from Musirawas, Muba, OKI, Muara Enim, and Banyuasin regencies. most of it is swamp land or about 1.42 million ha is peat land. Rice is the main food crop cultivated in Indonesia. One of the problems that are often encountered in the field that greatly affects rice productivity is weeds. Weeds are nuisance plants that grow around cultivated plants. This is the background for the creation of weed control innovations, namely by using Organic Planting Tape (OPT) as a rice planting medium. This study aims to determine the effect of OPT as an inhibitor of weed growth and determine the optimal width and thickness to inhibit weed growth. The experiment was arranged in a Randomized Block Design (RBD) with 3 groups and 5 treatments. Group I OPT width 20 cm, group II 30 cm, and group III 40 cm. While 1 was control (without OPT), treatment 2 was 4 mm thick, treatment 3 was 6 mm thick, and treatment 4 was 8 mm thick. This research was conducted from July to August 2019 in Mukti Jaya Village, Muara Telang District, Banyuasin Regency. carried out for 40 days. Observation of data obtained by analysis of variance or F test at 5% level. The results showed that the width and thickness of OPT had an effect on decreasing the number of weeds and weeds. OPT 40 cm wide and 8 mm thick did not produce the number of weeds that grew. The bigger and thicker the OPT, the more effective it is to deal with weeds.